Potensi Penerapan Interprofessional Collaboration Practice (IPC) Di Rumah Sakit Universitas Hasanuddin - Brajakson Siokal (Program Pascasarjana Universitas Muslim Indonesia, 2021)
Interprofessional collaboration practice is the interaction or relationship of two or more health professionals who work interdependently to provide care for patients, share information to make joint decisions, and find out the optimal time to collaborate in patient care. This study aims to determine the potential of health professionals in carrying out interprofessional collaboration practice at Hasanuddin University hospital. This research is a qualitative study with a phenomonological design. There were 7 (seven) participants in the study who were obtained through the use of purposive sampling technique. Data were analyzed using thematic analysis to determine the resulting themes. The results showed that through thematic analysis produced 4 (four) themes, including: basics of collaboration competence, success criteria for interprofessional collaboration practice, obstacles to implementing interprofessional collaboration practice, and expectations of health professionals on interprofessional collaboration practice.